Oxoplasma gondii: Of the myth to the reality in the farm animals - Jiménez Sanz, Amanda Lucía (Spei Domus, 2014)
Near third part of the world’s human population’s is positive to Toxoplasm gondi. Studies carried out in different countries shows as this protozoan parasite is found in most hot blooded animals, which includes the production and therefore human’s consumption animals. For a long time the domestic cat was seen as guilty of the transmission, but some investigations have demythologized this theory and shown that contagion can appear due to the consumption of raw or uncooked meats from contaminated animals, as well as because of water sources and floors in which the parasite is found, being able to survive during many months if conditions are favorable. Since 20 years there is a decrease observed in the presence of T. gondii in some species of consumption animals in developed countries, due to the technification and escalation of the production systems, which forces to work under confinement conditions.